Gene therapy for aromatic L-amino acid decarboxylase deficiency by MR-guided direct delivery of AAV2-AADC to midbrain dopaminergic neurons - Toni S. Pearson (Nature Portfolio, 2021)
Aromatic L-amino acid decarboxylase deficiency (AADC) is a rare neurodevelopmental disorder. Here the authors describe a clinical trial of MR-guided delivery of AAV2-AADC for the treatment of AADC.